Functionalization of glassy carbon spheres by ball milling of aryl diazonium salts - Pandurangappa, M; Ramakrishnappa, T; Compton, R (2009)
Solvent free derivatization has been achieved by a simple ball mill grinding procedure to functionalize glassy carbon spheres with anthraquinonyl and nitrophenyl groups using aryl diazonium salts. Grinding facilitates the mechanical activation of the carbon substrate material with the creation of active centres and may induce the decomposition of the diazonium salt. The functionalized glassy carbon spheres were characterized electrochemically by studying their cyclic voltammetry. These modified carbon spheres were also characterized by X-ray powder diffraction and Transmission electron microscopy to ascertain particle size reduction or change in surface morphology of the carbon spheres. The covalent attachment of these functional moieties to the surface of glassy carbon spheres were studied by X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. © 2009 Elsevier Ltd.